The Relationship Between Peer Social Support and Academic Procrastination Among Senior High School Students in SMA Negeri 1 Krueng Barona Jaya - Yadi Putra; Fauziah, Fauziah; Siti Humairah; Yusrika, Yusrika (Jurnal EduHealth, 2025)
Procrastination is a behaviour of delaying tasks that often occurs among students and has a negative impact on learning achievement. One external factor that can influence this behaviour is social support from peers. This study aims to determine the relationship between peer social support and academic procrastination among students at Krueng Barona Jaya State Senior High School 1. This study uses a quantitative approach with a cross-sectional design. The research population consisted of all 141 students in grades X and XI, with a sample of 59 students selected using proportional random sampling. The research instruments used were the Social Support Questionnaire (SSQ) and The Academic Procrastination Scale (APS). This study was conducted at SMA Negeri 1 Krueng Barona Jaya on 6–9 May 2025. The results showed that most students had moderate peer social support, with 24 students (40.7%) in this category and 35 students (59.3%) in the high category. Meanwhile, the level of academic procrastination among students was in the moderate category for 38 students (64.4%) and in the high category for 21 students (35.6%). The results of the Chi-Square test show a significant relationship between peer social support and academic procrastination with a p value of 0.001 (p ≤ 0.05). This means that the higher the social support from peers, the lower the level of academic procrastination among students. This study suggests that students should be more open and seek support from peers who motivate them to study, study together, remind each other, and reduce the habit of procrastinating, so that the learning process can run optimally and academic achievement can be improved.